Government Communication Patterns in Controlling Street Vendors in Banda Aceh City - Muhammad Syarif; Wahyu Rezeki; Zakaria; Zulfadli (Journal of Loomingulisus ja Innovatsioon, 2024)
One of the reasons is that there are still street vendors (PKL) disrupting public order in the city of Banda Aceh due to the lack of maximum good communication by the Satpol PP towards street vendors. So the focus of this research is related to the communication patterns of the Banda Aceh City Government in its efforts to control street vendors , and street traders’ perceptions of the Banda Aceh City Government’s communication patterns in their efforts to control street vendors. This research data comes from two Satpol PP and three street vendors. Data collection by means of observation, interviews and documentation. The results of the research show that so far the communication patterns used by the Government in controlling street vendors in Banda Aceh City use vertical communication patterns and horizontal communication patterns. Meanwhile, street vendors’ perceptions of the communication patterns used by the Banda Aceh City Government are classified as good or have a positive perception, because they carry out control using a persuasive approach.